Asbab Al-Nuzul fi Mandur Nurcholish Madjid Al-Indunisiy - Zaky Mumtaz Ali (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2021)
This article aims to study the views of Nurcholish Madjid in the concept of Asbab Al-Nuzul and how these views have influenced his deals with the Holy Qur’an. The researcher adopted the method of induction and analysis to study this topic, where the researcher collected the writings of Nurcholish Madjid related to the causes of revelation, and then analyzed these writings to get out of them with the expected results. Among the most important of his writings on the causes of revelation is his article "Konsep Asbab Al-Nuzul Relevansinya bagi Pandangan Historis Segi-Segi Tertentu Pandangan Keagamaan", in his book "Kontekstualisasi Doktrin Islam dalam Sejarah". Perhaps one of the most important results of this research is that Nurcholish Madjid has expanded a lot in the circle of Asbab Al-Nuzul, as he sees that there are general reasons for the revelation of the Qur’an that include the social, cultural and political conditions in the Arabian Peninsula at the time of revelation, and then proceeds from this idea to new jurisprudence in the religion fields.